2001
DOI: 10.1046/j.1440-1746.2001.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis in chronic hepatitis C virus infection: Prevalence and clinical correlation

Abstract: It was found that 52% of Chinese patients with chronic hepatitis C had hepatic steatosis. Patients with hepatic steatosis were more frequently obese and had more severe hepatic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
123
4
17

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 34 publications
16
123
4
17
Order By: Relevance
“…However, a study performed by Preumalswami et al, 2006 suggested that hepatic steatosis was not related to hepatic fibrosis in CHC infection. Hwang et al, 2001 have pointed out that the stage of hepatic fibrosis is generally advanced in patients with hepatic steatosis compared to those without steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, a study performed by Preumalswami et al, 2006 suggested that hepatic steatosis was not related to hepatic fibrosis in CHC infection. Hwang et al, 2001 have pointed out that the stage of hepatic fibrosis is generally advanced in patients with hepatic steatosis compared to those without steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…45 The influence of overweight has been emphasized recently; it is believed that steatosis related to overweight is responsible for the more rapid progression of fibrosis. [46][47][48] In addition, diabetes has been shown to be associated with fibrosis. 49 …”
Section: Factors Associated With Fibrosis Progressionmentioning
confidence: 99%
“…Factors like obesity, type 2 diabetes and hepatic steatosis predispose to both NASH as well as fibrotic progression in hepatitis C [30,31] . Obesity is recognised now as an independent risk factor for development of alcoholic cirrhosis [32].…”
Section: Discussionmentioning
confidence: 99%